Etravirine in treatment‐experienced, HIV‐1‐infected children and adolescents: 48‐week safety, efficacy and resistance analysis of the phase II PIANO study. Issue 9 (3rd March 2014) - Tudor‐Williams, G; Cahn, P; Chokephaibulkit, K; Fourie, J; Karatzios, C; Dincq, S; Opsomer, M; Kakuda, TN; Nijs, S; Tambuyzer, L; Tomaka, FL; PIANO study group
<x xml:space="preserve">Abstract</x> Objectives PIANO (Paediatric study of Intelence As an NNRTI Option; TMC125‐C213; NCT00665847) assessed the safety/tolerability, antiviral activity and pharmacokinetics of etravirine plus an optimized background regimen (OBR) in treatment‐experienced, HIV‐1‐infected children (≥ 6 to < 12 years) and adolescents (≥ 12 to < 18 years) over 48 weeks. Methods In a phase II, open‐label, single‐arm study, 101 treatment‐experienced patients (41 children; 60 adolescents) with screening viral load (VL) ≥ 500 HIV‐1 RNA copies/mL received etravirine 5.2 mg/kg (maximum dose 200 mg) twice a day (bid) plus OBR. Results Sixty‐seven per cent of patients had previously used efavirenz or nevirapine. At week 48, the most common treatment‐related grade ≥ 2 adverse event (AE) was rash (13%); 12% experienced grade 3 AEs. Only two grade 4 AEs occurred (both thrombocytopaenia, not etravirine related). At week 48, 56% of patients (68% children; 48% adolescents) achieved a virological response (VL<50 copies/mL; intent‐to‐treat, noncompleter=failure). Factors predictive of response were adherence > 95%, male sex, low baseline etravirine weighted genotypic score and high etravirine trough concentration (C0h). Seventy‐six patients (75%) completed the trial; most discontinuations occurred because of protocol noncompliance or AEs (8% each). Sixty‐five per cent of patients were > 95% adherent by questionnaire and 39% by pill count. Forty‐one patients experienced virological failure (VF; time‐to‐loss‐of‐virological‐response non‐VF‐censored algorithm) (29 nonresponders; 12 rebounders). Of 30 patients with VF with paired baseline/endpoint genotypes, 18 (60%) developed nonnucleoside reverse transcriptase inhibitor (NNRTI) mutations, most commonly Y181C. Mean etravirine area under the plasma concentration–time curve over 12 h (AUC0–12h; 5216 ng h/mL) and C0h (346 ng/mL) were comparable to adult target values. Conclusions Results with etravirine 5.2 mg/kg bid (with OBR) in this treatment‐experienced paediatric population and etravirine 200 mg bid in treatment‐experienced adults were comparable. Etravirine is an NNRTI option for treatment‐experienced paediatric patients.